Development of a rapid DNA extraction method and one-step nested PCR for the detection of Naegleria fowleri from the environment - Ahmad, A.F.; Lonnen, J.; Andrew, P.W.; Kilvington, S. (2011)
Naegleria fowleri is a small free-living amoebo-flagellate found in natural and manmade thermal aquatic habitats worldwide. The organism is pathogenic to man causing fatal primary amoebic meningoencephalitis (PAM). Infection typically results from bathing in contaminated water and is usually fatal. It is, therefore, important to identify sites containing N. fowleri in the interests of preventive public health microbiology. Culture of environmental material is the conventional method for the isolation of N. fowleri but requires several days incubation and subsequent biochemical or molecular tests to confirm identification. Here, a nested one-step PCR test, in conjunction with a direct DNA extraction from water or sediment material, was developed for the rapid and reliable detection of N. fowleri from the environment. Here, the assay detected N, fowleri in 18/109 river water samples associated with a nuclear power plant in South West France and 0/10 from a similar site in the UK. Although culture of samples yielded numerous thermophilic free-living amoebae, none were N. fowleri or other thermophilic Naegleria spp. The availability of a rapid, reliable and sensitive one-step nested PCR method for the direct detection of N. fowleri from the environment may aid ecological studies and enable intervention to prevent PAM cases. Crown Copyright (C) 2011 Published by Elsevier Ltd. All rights reserved.